The foundation of the first amphitheatre of the Faculty of Pharmacy in Cluj - Bârsu, Cristian (Medicine and Pharmacy Reports, 2013)
The Faculty of Pharmacy of Cluj was created in 1948. The first dean was Erwin Popper (1906-1974) – professor of analytical chemistry. At the beginning of the activity the didactic spaces in this institution were not sufficient. Consequently, Prof. Popper tried and succeeded in solving this problem. In 1955-1957, despite financial and economic difficulties, he succeeded in raising a new building for the departments of Analytical Chemistry and Physical Chemistry. The most important part of this edifice was a modern, large and elegant amphitheatre of 200 places. This was the first lecture hall of the Faculty. The historical value of this amphitheatre was completed in 1957 with bass relief carvings, representing important pharmacists and chemists, such as Carol Davila, Ştefan Minovici, Constantin I. Istrati, Nicolae Teclu, Ion Vintilescu and Gheorghe Spacu. The artistic representations of these Romanian scientists were created by Virgil Fulicia (1907-1979) – professor of the Fine Arts Academy in Cluj.